CLIMATE CHANGE ADAPTATION STRATEGIES AND AGRICULTURE IN ANAMBRA STATE, NIGERIA - Effiong, M; Akwo, Theresa (FUDMA Journal of Sciences, 2026)
Most crop farmers experience low crop yields due to extreme weather conditions such as high and fluctuating rainfall patterns, flooding, droughts, high temperatures, and other disparaging weather conditions caused by climate change. The study specifically examined the use of climate change adaptation strategies among these farmers, analyzed the determinants of crop farmers’ involvement in climate change adaptation practices in the state, estimated the effects of climate change adaptation practices on their income and, determined factors affecting the volume of investments in climate change adaptation practices in the study area. The study adopted a survey design. The multi-stage sampling technique was used to select 100 respondents. Data were analyzed using probit and Ordinary Least squares multiple regression. The climate change adaptation strategies were the use of wetland (18.14), afforestation (27.73), while the use of resistant varieties (-121839.60), increased use of fertilizers (96642.13), moving to a different site (291119.50), and erosion control (102061.3) significantly affected their income. The socioeconomic factors that significantly influenced the volume of investments to the climate change adaptation practices among the crop farmers included: age of the crop farmers (-0.03), marital status (6467.17), educational level (1442.87), household size (1193.01), primary occupation (188.99), farm size (1824.09) and income (24258.42). It was recommended that crop farmers use indigenous climate change adaptation practices.
Keywords: Economic assessment; climate change; adaptation strategies; crop farmers